Etiological diagnoses of out-of-hospital cardiac arrest survivors admitted to the intensive care unit: Insights from a French registry. (August 2017) - Geri, Guillaume; Passouant, Olivier; Dumas, Florence; Bougouin, Wulfran; Champigneulle, Benoit; Arnaout, Michel; Chelly, Jonathan; Chiche, Jean-Daniel; Varenne, Olivier; Guillemet, Lucie; Pène, Frederic; Waldmann, Victor; et al.
Abstract: Background: Respective proportions of final etiologies are disparate in cohorts of cardiac arrest patients, depending on examined population and diagnostic algorithms. In particular, prevalence and characteristics of sudden unexplained death syndrome (SUDS) are debated. We aimed at describing etiologies in a large cohort of aborted out-of-hospital cardiac arrest (OHCA) patients, in order to assess prevalence and outcome of SUDS. Patients and methods: We analyzed data from our prospective registry of successfully resuscitated OHCA patients admitted to a cardiac arrest centre between January 2002 and December 2014. The in-ICU diagnostic strategy included early coronary angiogram, brain and chest CT scan. This was completed by an extensive diagnostic strategy, encompassing biological and toxicological tests, repeated electrocardiograms and echocardiography, MRI and pharmacologic tests. Two independent investigators reviewed each final diagnosis. Baseline characteristics were compared between subgroups of patients. Three-month mortality was compared between subgroups using univariate Kaplan-Meier curves. Results: Over the study period, 1657 patients were admitted to our unit after an aborted OHCA. The event was attributed to a non-cardiac and a cardiac cause in 478 (32.0%) and 978 (65.5%) patients, respectively. The main cause of cardiac related OHCA was ischemic heart disease (76.7%) while primary electrical diseases accounted for only 2.5%. Sudden unexplained deaths (SUDS) were observed in 37 (2.5%) patients. Conclusion: We observed that ischemic heart disease was by far the most common cause of cardiac arrest, while primary electrical diseases were much less frequent. SUDS accounted for a very small proportion of patients who suffered an aborted OHCA.